Gender based outcome of IABP implantation in patients with acute coronary syndrome and cardiogenic shock: a national inpatient sample database analysis. (14th October 2021) - Patel, N; Amgai, B; Chakraborty, S; Hajra, A; Aryal, B; Patel, Z; Ashish, K; Reddy, M; Aronow, W; Khalid, M
Abstract: Background: Intra-Aortic Balloon counter-pulsation is frequently used as a circulatory support device in patients requiring hemodynamic support - in cardiogenic shock and in patients at risk of hemodynamic decompensation during a high-risk coronary intervention. Impact of IABP in this patient population has been variable. Certain studies have shown a beneficial effect of IABP on selected populations having acute coronary syndrome with cardiogenic shock (1–3). Our objective was to compare the outcomes based on gender in the ACS population with cardiogenic shock and IABP placement. Methods: We analyzed the National Inpatient Sample database from Oct-2015 to Dec-2017 released under Healthcare Cost utilization Project in the USA using Stata 16.0. The population was identified using respective ICD-10 codes. We excluded the population with sudden cardiac arrest, pulmonary embolism, and patients with anatomical post-MI complications. Multivariate logistic regression analysis was done to determine the difference in outcomes based on gender using clinically relevant variables. Later, propensity-matched cohort analysis was performed based on the regression variables. Results: Of 36, 990 patients who met our inclusion criteria 25, 670 (69%) were male and 11, 320 (31%) were female. The average age for male and female populations was 66±11 and 69±12 years. Femnales were more likely to have higher Charlson co-morbidity index three or above. We found higher mortality in the female population [3, 146 (27.79%)] compared to male [5, 884 (22.92%)] in univariate analyses. Propensity-matched multivariate regression analysis showed no difference [OR: 1.06 (0.91–1.22) with P-value: 0.482] in mortality after adjusting for clinically relevant variables. Subgroup analysis in STEMI and NSTEMI populations did not show a difference. The average hospital stay was similar in both cohorts, with the male having a higher cost per stay. We found no difference in most of the complications included in our study except for higher coronary artery dissection [OR: 2.98 (1.73–5.13), P-value: <0.001] and lower rates of AKI [OR: 0.72 (0.63–0.83), P-value: <0.001], AKI requiring hemodialysis [OR: 0.74 (0.56–0.97), P-value:0.031] and ventricular tachycardia [OR: 0.73 (0.64–0.84), P-value: <0.001] in the female population. Conclusion: The inpatient population of ACS with Cardiogenic shock and IABP insertion showed no significant difference in mortality between males and females which was valid for subgroup analysis of NSTEMI and STEMI groups. Complications such as coronary artery dissection were higher, whereas AKI, AKI requiring hemodialysis, and ventricular tachycardias, were lower in females than males. FUNDunding Acknowledgement: Type of funding sources: None.